Comment: Embodied Emotions From a Dutch Historical Perspective. (July 2016) - Leemans, Inger
This comment challenges essentialist "brain biased" interpretations of emotions from a historical perspective. (Digital) humanities research shows that the embodying of emotions is historically contingent. Emotion metaphors do not so much reflect what is happening in our brain or in other parts of the body: they reflect what people think/thought is/was happening in and outside their body.